36th Annual Hawaii International Conference on System Sciences, 2003. Proceedings of The 2003
DOI: 10.1109/hicss.2003.1174250
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bilingual term list size on dictionary-based cross-language information retrieval

Abstract: Bilingual term lists are extensively used as a resource for dictionary-based Cross-Language Information Retrieval (CLIR)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…For TDT-2003 we plan to incorporate the best results from our Arabic-English TREC-2002 CLIR system and from our earlier work on MandarinEnglish translingual topic tracking. Given the importance of proper names to detection in news stories [6], we are also interested in exploring the effect of more sophisticated transliteration techniques than we tried this year.…”
Section: Resultsmentioning
confidence: 99%
“…For TDT-2003 we plan to incorporate the best results from our Arabic-English TREC-2002 CLIR system and from our earlier work on MandarinEnglish translingual topic tracking. Given the importance of proper names to detection in news stories [6], we are also interested in exploring the effect of more sophisticated transliteration techniques than we tried this year.…”
Section: Resultsmentioning
confidence: 99%
“…The focus on the third stage has been somewhat more recent, with the best presently known technique based on accumulating term frequency and document frequency evidence separately in the document language, then combining that evidence to create query-language term weights [6].…”
Section: E Bilingual Dictionarymentioning
confidence: 99%
“…For the first stage, the best results are typically obtained by translating multiword expressions when possible, backing off to individual words when necessary, and further backing off to morphological roots when the surface form cannot be found [6].…”
Section: E Bilingual Dictionarymentioning
confidence: 99%
See 1 more Smart Citation
“…The most directly comparable translation resource that we used was a manually created clean bilingual term list obtained from the Internet. That bilingual term list contains 30,322 unique translation pairs, which several studies have shown to be enough to approach a point of diminishing returns in cross-language retrieval applications [7].…”
Section: Cross Language Retrieval Applicationsmentioning
confidence: 99%